SI LUHUR: Improving digitalization-based public services in Sidoluhur Village, Malang - Handayani Nur Hayati; Akbar Pandu Dwinugraha; Sinta Nur Fiasari; Hana Jihan Khoirunnisa; Maria Florida Evalista (Community Empowerment, 2023)
Sidoluhur Village, Lawang District, Malang Regency has the majority of the population working as farm labourers. With a population of 6,182 people consisting of around 1,978 heads of households, this village has problems with administrative activities and public services. The purpose of this activity is to increase the competence of village officials in providing digital-based administrative services. The method used is Participatory Rural Appraisal (PRA). The result obtained from this activity is that there is an application ‘SI LUHUR’ to support public services. Village apparatus and the community are able to carry out and access digital-based public services. In addition, this activity also increases the solidity and synergy of village apparatus in managing public services.